Mapping Allele-Specific DNA Methylation: A New Tool for Maximizing Information from GWAS - Tycko, Benjamin (Elsevier, 2010)
In this issue of The Journal, an article by Schalkwyk et al.(1) shows the landscape of allele-specific DNA methylation (ASM) in the human genome. ASM has long been studied as a hallmark of imprinted genes, and a chromosome-wide version of this phenomenon occurs, in a random fashion, during X chromosome inactivation in female cells. But the type of ASM motivating the study by Schalkwyk et al. is different. They used a high-resolution, methylation-sensitive SNP array (MSNP) method for genome-wide profiling of ASM in total peripheral-blood leukocytes (PBL) and buccal cells from a series of monozygotic twin pairs. Their data bring a new level of detail to our knowledge of a newly recognized phenomenon—nonimprinted, sequence-dependent ASM. They document the widespread occurrence of this phenomenon among human genes and discuss its basic implications for gene regulation and genetic-epigenetic interactions. But this paper and recent work from other laboratories(2,3) raises the possibility of a more immediate and practical application for ASM mapping, namely to help extract maximum information from genome-wide association studies.